Towards Elimination of Mother-to-Child Transmission of HIV: The Impact of a Rapid Results Initiative in Nyanza Province, Kenya - Lisa L. Dillabaugh; Jayne Lewis Kulzer; Kevin Owuor; Valerie Ndege; Arbogast Oyanga; Evelyne Ngugi; Starley B. Shade; Elizabeth Bukusi; Craig R. Cohen (AIDS Research and Treatment)
Many HIV-positive pregnant women and infants are still not receiving optimal services, preventing the goal of eliminating mother-to-child transmission (MTCT) and improving maternal child health overall. A Rapid Results Initiative (RRI) approach was utilized to address key challenges in delivery of prevention of MTCT (PMTCT) services including highly active antiretroviral therapy (HAART) uptake for women and infants. The RRI was conducted between April and June 2011 at 119 health facilities in five districts in Nyanza Province, Kenya. Aggregated site-level data were compared at baseline before the RRI (Oct 2010–Jan 2011), during the RRI, and post-RRI (Jul–Sep 2011) using pre-post cohort analysis. HAART uptake amongst all HIV-positive pregnant women increased by 40% (RR 1.4, 95% CI 1.2–1.7) and continued to improve post-RRI (RR 1.6, 95% CI 1.4–1.8). HAART uptake in HIV-positive infants remained stable (RR 1.1, 95% CI 0.9–1.4) during the RRI and improved by 30% (RR 1.3, 95% CI 1.0–1.6) post-RRI. Significant improvement in PMTCT services can be achieved through introduction of an RRI, which appears to lead to sustained benefits for pregnant HIV-infected women and their infants.